RoboPol: connection between optical polarization plane rotations and gamma-ray flares in blazars. Issue 1 (26th October 2017) - Blinov, D.; Pavlidou, V.; Papadakis, I.; Kiehlmann, S.; Liodakis, I.; Panopoulou, G. V.; Angelakis, E.; Baloković, M.; Hovatta, T.; King, O. G.; Kus, A.; Kylafis, N.; et al.
Abstract: We use results of our 3 yr polarimetric monitoring programme to investigate the previously suggested connection between rotations of the polarization plane in the optical emission of blazars and their gamma-ray flares in the GeV band. The homogeneous set of 40 rotation events in 24 sources detected by RoboPol is analysed together with the gamma-ray data provided by Fermi -LAT. We confirm that polarization plane rotations are indeed related to the closest gamma-ray flares in blazars and the time lags between these events are consistent with zero. Amplitudes of the rotations are anticorrelated with amplitudes of the gamma-ray flares. This is presumably caused by higher relativistic boosting (higher Doppler factors) in blazars that exhibit smaller amplitude polarization plane rotations. Moreover, the time-scales of rotations and flares are marginally correlated.